La parentalité, une contribution au capital des femmes des classes supérieures ? - Julie Landour (Genre, Sexualité et Société)
This article proposes to consider parental engagement as a cultural resource. Through this perspective, embracing the contemporary norms that define parenting participates in constituting a distinctive cultural capital that hierarchizes parents, considered as good or bad. Studies on parenting have mainly focused on women belonging to the lower classes; here we examine its sociological grounds and its social and political consequences through the case of mompreneurs. The situation of these women belonging to the upper-middle and upper classes is characterized by the creation of a self-waged employment on the occasion of a pregnancy. Based on a three-year ethnography and fifty biographical interviews, this article questions maternity in the light of parental engagement and cultural capital, and analyzes its distinctive dimensions and political ambivalences.